Modern Ethiopia and Colonial Eritrea - Taddia, Irma (Aethiopica, 2002)
The article develops some reflections on present-day Eritrea in the light of the colonial past and in the context of modern Ethiopia. If we consider Eritrea and its path towards independence, some differences and analogies emerge in comparison with other African colonies. The Eritrean independence is taking place today in a very specific context in post-colonial Africa. It is not a simple case of delayed decolonization, postponed by 30 years with respect to other former African colonies. The history of Eritrea must be studied within the colonial context: colonialism created a national identity, but Eritrea is a colony that did not become an independent state. This phenomenon can be attributed to various causes which I will try to underline. The process of state formation in Eritrea raises some problems for historians. The construction of a new political legitimacy is strictly connected to the birth of a national historiography in the country. I would like to examine in a critical way the process of writing history in contemporary Eritrea. Reconstructing the history of the past goes beyond the reconstruction of the history of the Eritrean state today. We have to consider the entire area – the Horn of Africa – in the pre-colonial period. The paper discusses the interrelation between the creation of the state and the national historiography.